Effect of Internal and External Factors on Profitability in Sharia Business Units (UUS) PT. Bank Tabungan Negara (Persero) Tbk - Wahyudi Gusti Antony; Harlen Harlen; Yusni Maulida (Indonesian Journal of Economics, Social, and Humanities, 2021)
This study studied to analyze the factors that influence the ROA at the UUS Bank BTN seen from internal factors as well as from external banks. Related to internal bank factors, namely Non Performing Financing (NPF), and Intellectual Capital, and bank external factors which contain Inflation, and Bank Indonesia Interest Rates. The research period from 2006 to 2017. The data used was obtained from the Annual Publication Financial Report with data collection techniques by means of coordination, so that the research data sample was 12. Data analysis techniques used were multiple linear regression. The results of the study show that all variables, namely NPF, Intellectual Capital, Inflation, and Interest Rate of Bank Indonesia affect ROA simultaneously. Partial inflation, and Bank Indonesia interest rates do not affect the temporary ROA of NPF, and intellectual capital influences ROA significantly. From independent independent variables that oppose the submission of opinions on the ROA owned by NPF which has the greatest influence with a coefficient of -0,353338%. Next Intellectual Capital with a coefficient of 0,107804%.